Characterization of pyrolytic oil from catalytic pyrolysis of waste tyre and empty fruit bunch / Muhammad Nor Sobri Ruslan - Ruslan, Muhammad Nor Sobri (2010)
Co-pyrolysis was discovered as a new technology to dispose solid waste with valuable yield. In this study, co-pyrolysis of waste tire and empty fruit bunches (EFB) was investigated using fixed bed rector at 500 'C The effects of the catalyst on the yields of the products were investigated. The products obtained from pyrolysis of waste tire and EFB were 42.8% of liquid oil, 33.2% of char and 24% of gas fraction. The calorific value, ash, moisture content, volatile matter, fixed carbon and elemental analysis of raw sample were determined. The oil yield was found to be increased from 42.8% to 57.06% after the addition of 1:1 ratio of cobalt catalyst impregnated into the empty fruit bunch, where as no significant increment on the residue (char). The properties of the oil were determined by gas chromatography mass spectrometer (GCMS). Limonene was identified as a major compound of the oils representing 18.41% of peak areas. Significant quantities of light aromatic hydrocarbon such as benzene, toluene, xylene, and styrene were also found.